Distribution of serotypes, penicillin susceptibilities and virulence genes in Streptococcus pneumoniae isolates from Malaysian healthy children - Mohamed Shakrin, Nik Noorul Shakira; Mohd Yatim, Masura; Masri, Siti Norbaya; Mohd Taib, Niazlin; Jamal, Farida Fatema @ Farida; Mohd Desa, Mohd Nasir (2012)
This study was carried out to analyze the distribution of serotypes, penicillin susceptibilities, and virulence genes among nasal carriage of Streptococcus pneumoniaefrom Malaysian healthy children. Fifty isolates were obtained from nasal swabs of children aged 5 years and younger who attended 3-day care centers in Kuala Lumpur, Malaysia from June to December 2010. The isolates were serotyped using commercial antisera. Minimum inhibitory concentrations (MICs) for penicillin of the isolates were then determined by E test followed by polymerase chain reaction (PCR)- screening for 8 virulence (LytA, Ply, PsaA, PspA, cbp A, cbp G, PavA & rlr) and 3 penicillin-binding protein (pbp La, 2b and 2x) genes. The later were further subjected to restriction-fragment-Iength-polymorphism (RFLP)analysis and compared against the penicillin susceptibility of the isolates. Among the 50 isolates, 11 serotypes were identified with serotype 6A been the most common, 2 isolates were non-typeable. 28 (56%) were penicillin susceptible (PSSP), 6 (12%) were intermediate (PISP) and 16 (32%) were resistant (PRSP).PRSPwas high among serotypes 6A (68.75%) followed by 23F (25%) and non-typeable (6.25%). The 8 virulence genes were detected in all isolates except for rlr gene; 8 (16%). PCR-RFLPanalvsis showed different pbp-gene patterns among the PRSPs which is consistent with the altered pbp-genes. Therefore, this study indicates that, with such phenotypic and genotypic pattern, the nasal isolates have potential to institute infection among this high group of the population.